Disentangling drought-induced variation in ecosystem and soil respiration using stable carbon isotopes. (Oecologia, 2010)
Combining C flux measurements with information on their isotopic composition can yield a process-based understanding of ecosystem C dynamics. We studied the variations in both respiratory fluxes and their stable C isotopic compositions (delta(13)C) for all major components (trees, understory, roots and soil microorganisms) in a Mediterranean oak savannah during a period with increasing drought. We found large drought-induced and diurnal dynamics in isotopic compositions of soil, root and foliage respiration (delta(13)C(res)). Soil respiration was the largest contributor to ecosystem respiration (R (eco)), exhibiting a depleted isotopic signature and no marked variations with increasing drought, similar to ecosystem respired delta(13)CO(2), providing evidence for a stable C-source and minor influence of recent photosynthate from plants. Short-term and diurnal variations in delta(13)C(res) of foliage and roots (up to 8 and 4 per thousand, respectively) were in agreement with: (1) recent hypotheses on post-photosynthetic fractionation processes, (2) substrate changes with decreasing assimilation rates in combination with increased respiratory demand, and (3) decreased phosphoenolpyruvate carboxylase activity in drying roots, while altered photosynthetic discrimination was not responsible for the observed changes in delta(13)C(res). We applied a flux-based and an isotopic flux-based mass balance, yielding good agreement at the soil scale, while the isotopic mass balance at the ecosystem scale was not conserved. This was mainly caused by uncertainties in Keeling plot intercepts at the ecosystem scale due to small CO(2) gradients and large differences in delta(13)C(res) of the different component fluxes. Overall, stable isotopes provided valuable new insights into the drought-related variations of ecosystem C dynamics, encouraging future studies but also highlighting the need of improved methodology to disentangle short-term dynamics of isotopic composition of R (eco).